2011
DOI: 10.1177/1049909111412580
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Hospice for Children as Perceived by Hospice Organizations in North Carolina

Abstract: Despite improving organization of hospice for children with life-limiting illnesses, services may be underutilized. We asked representatives of all 76 existing North Carolina hospice organizations about barriers to serving children. Representatives of 61 agencies responded (80%). Hospices serving children differed from hospices not serving children on perception of barriers: 1) Lack of pediatric trained staff (8% vs 42%, p = 0.01); 2) lack of pediatrician consultation (23% vs 50%, p = 0.03); 3) lack of pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…This finding likely speaks to a lack of hospice facilities with pediatric expertise in the United States . To date, only 14% of participating hospice agencies report having formal pediatric PC services with specialized staff, and a number of educational, procedural, and sociocultural barriers further impede provision of community‐based EOL care for children and families . Development and implementation of interventions to improve access to pediatric PC and hospice in the community is a valuable area of research that remains largely unexplored …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding likely speaks to a lack of hospice facilities with pediatric expertise in the United States . To date, only 14% of participating hospice agencies report having formal pediatric PC services with specialized staff, and a number of educational, procedural, and sociocultural barriers further impede provision of community‐based EOL care for children and families . Development and implementation of interventions to improve access to pediatric PC and hospice in the community is a valuable area of research that remains largely unexplored …”
Section: Discussionmentioning
confidence: 99%
“…70,71 To date, only 14% of participating hospice agencies report having formal pediatric PC services with specialized staff, 71 and a number of educational, procedural, and sociocultural barriers further impede provision of community-based EOL care for children and families. 72 Development and implementation of interventions to improve access to pediatric PC and hospice in the community is a valuable area of research that remains largely unexplored. 73 Importantly, three-quarters of PPO patients at this institution had PC involvement prior to the LMOL, with the median time between initial consultation and death falling at approximately 2.5 months.…”
Section: Association Between Timing Of Pc Involvement Before Death Anmentioning
confidence: 99%
“…In addition, few hospice programs in the United States advertise the provision of pediatric services, and those that do may have such a low pediatric census that they fail to acquire or maintain comfort and expertise with this patient population . Despite increasing community‐based needs, the percentage of hospices offering pediatric care actually decreased from 2002 to 2008, and increasing competition among hospices has been associated with a decreased probability of having pediatric services .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that hospice care provides physical and psychosocial benefits for children and their families (34). Despite the potential value of hospice care for children, it is estimated that approximately 90% of children who may benefit from hospice services never receive it, and as few as 40% of community-based hospices provide care to children (5–6). …”
Section: Introductionmentioning
confidence: 99%